2017
DOI: 10.17011/apples/urn.201702061368
|View full text |Cite
|
Sign up to set email alerts
|

Emerged challenges for English education in Japan

Abstract: Although Japanese students study English

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 4 publications
0
5
0
Order By: Relevance
“…This is encouraging since it allows teachers to provide a more complete, and arguably, a more engaging language-learning experience while also not overwhelming them if they are lower in proficiency level. Going forward, as the average proficiency level of first-year university students in Japan continues to decline (see Suzuki, 2017), solutions such as this may become all the more important.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This is encouraging since it allows teachers to provide a more complete, and arguably, a more engaging language-learning experience while also not overwhelming them if they are lower in proficiency level. Going forward, as the average proficiency level of first-year university students in Japan continues to decline (see Suzuki, 2017), solutions such as this may become all the more important.…”
Section: Resultsmentioning
confidence: 99%
“…If teachers in Japan see fit to incorporate techniques and activities which aim to promote active learning, then learners in these call classes need to be accepting of the different techniques and activities and the need for perhaps less class time being available for unit completion. Another reason why it is encouraging is another finding reported by Suzuki (2017), sourced from the Institution of National Educational Policy (2014). It indicated that "51.2 percent of Japanese university students had not experienced group work or expressed their thoughts in English before they entered university" (p. 7).…”
Section: Active Learningmentioning
confidence: 85%
See 1 more Smart Citation
“…) are examined, the fact that students are demotivated to learn English is seen to a common factor. (Ali & Pathan, 2017;Hojaji & Salehi, 2017;Suzuki, 2017). However, it is known that there have been problems in English education in Turkey for many years.…”
Section: Discussionmentioning
confidence: 99%
“…10, No. 8;2017 demotivation-related studies in L2 learning are largely based on Dörnyei's studies. Described by Dörnyei as the decrease of motivation in L2 learning due to external factors, demotivation shows up as effect of varying factors.…”
Section: Demotivation In Language Learningmentioning
confidence: 99%